On the Cox ring of $P^2$ blown up in points on a line - Ottem, John Christian (MATHEMATICA SCANDINAVICA, 2011)
We show that the blow-up of $P^2$ in $n$ points on a line has finitely generated Cox ring. We give explicit generators for the ring and calculate its defining ideal of relations.